2018
DOI: 10.1530/rep-17-0507
|View full text |Cite
|
Sign up to set email alerts
|

Murine sperm capacitation, oocyte penetration and decondensation following moderate alcohol intake

Abstract: Male chronic alcohol abuse causes testicular failure and infertility. We analyzed the effects of moderate sub-chronic alcohol intake on sperm morphology, capacitation, fertilization and sperm head decondensation. CF-1 male mice were administered 15% ethanol in drinking water for 15 days; control mice received ethanol-free water. Similar patterns of tyrosine phosphorylation were observed in capacitated spermatozoa of control and treated males. Percentage of hyperactivation (H) and spontaneous (SAR) and progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Besides the alterations in the semen quality (lower sperm concentration, motility, and percentage of normal forms), Rahimipour et al also reported reduced DNA condensation and integrity in mice fed with ethanol compared to controls, along with increased apoptotic rates [ 85 ]. In addition, in vitro experiments showed an accelerated acrosomal loss occurring during the sperm capacitation of human and animal sperm incubated in ethanol, further reducing their fertilizing ability [ 124 , 125 , 126 , 127 ]. This is probably due to the capacity of ethanol to alter lipid fluidity and membrane permeability through the oxidation of the membranes’ lipids and proteins [ 127 ].…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the alterations in the semen quality (lower sperm concentration, motility, and percentage of normal forms), Rahimipour et al also reported reduced DNA condensation and integrity in mice fed with ethanol compared to controls, along with increased apoptotic rates [ 85 ]. In addition, in vitro experiments showed an accelerated acrosomal loss occurring during the sperm capacitation of human and animal sperm incubated in ethanol, further reducing their fertilizing ability [ 124 , 125 , 126 , 127 ]. This is probably due to the capacity of ethanol to alter lipid fluidity and membrane permeability through the oxidation of the membranes’ lipids and proteins [ 127 ].…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 99%
“…In addition, in vitro experiments showed an accelerated acrosomal loss occurring during the sperm capacitation of human and animal sperm incubated in ethanol, further reducing their fertilizing ability [ 124 , 125 , 126 , 127 ]. This is probably due to the capacity of ethanol to alter lipid fluidity and membrane permeability through the oxidation of the membranes’ lipids and proteins [ 127 ]. In rats, decreased sperm motility was observed after exposure to EtOH, as well as changes in the meiotic divisions, reduced gametes viability, and a higher rate of sperm with poorly condensed chromatin [ 86 , 87 ].…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 99%
“…Alcohol exposure has adverse effects on the reproductive system of females and males [ 22 , 23 ], and can also cause abnormal preimplantation embryo development. In our current society, more and more preadolescent women are inevitably exposed to alcohol [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the incubation period, the oocytes were fixed in 2% PFA diluted in CMF-PVP 0.4% and were then stained with 0.1 mM Hoechst 33342 in the dark for 20 min at RT. After washing, oocytes were examined under phase contrast and fluorescence microscopy (Axioplan Zeiss) and were classified as described in Sanchez et al and Rosenbusch et al …”
Section: Methodsmentioning
confidence: 99%